2013
DOI: 10.7314/apjcp.2013.14.4.2277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Breast Density and Volume on Breast Cancer Diagnosis: A Retrospective Comparison of Sensitivity of Mammography and Ultrasonography in China's Rural Areas

Abstract: Purpose: Mammography has been confirmed as the only effective mode to improve the prognosis of patients with breast cancer in Western developed countries, but might not be a good choice in other areas of the world. One of the major challenges in China is to determine an optimal imaging modality for breast cancer screening. This study was designed to clarify the sensitivity of ultrasonography compared with that of mammography in rural China. Methods: We retrospectively studied the sensitivity of mammography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
6
25
1
Order By: Relevance
“…This revealed the limitation of mammography that sensitivity decreased in dense breast. Wang FL et al revealed that ultrasonography is more sensitive than mammography in women under 55 year-old, especially in those with high-density breast (Wang et al, 2013). Still there were another mammographic data of malignant tumors affected by age.…”
Section: Discussionmentioning
confidence: 99%
“…This revealed the limitation of mammography that sensitivity decreased in dense breast. Wang FL et al revealed that ultrasonography is more sensitive than mammography in women under 55 year-old, especially in those with high-density breast (Wang et al, 2013). Still there were another mammographic data of malignant tumors affected by age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with regard to the Chinese women in younger than 55 years old, the addition of other modalities such as ultrasound may provide some potential benefits in the sensitivity, specificity as well as diagnostic accuracy of the detection and characterization of early stage breast cancer. A recent research (Wang et al, 2013) reported that ultrasonography was markedly more effective than mammography for most Chinese women who were younger than 55 years old. Recently, the State Legislatures of Connecticut, Texas, Virginia, California and New York passed laws requiring physicians to tell women whether they have dense tissue based on mammographic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Breast US is widely available, painless, well-tolerated, relatively inexpensive, and does not involve ionizing radiation (Berg et al, 2008). Supplemental screening using breast US increased the detection of early, node-negative, invasive breast cancers not normally seen on mammography in women with dense parenchyma (Benson et al, 2004;Berg et al, 2004;Wang et al, 2013). However, the dependence on operator technique for hand-held ultrasound (HHUS) is a major concern when considering the widespread use of whole-breast US (Akbari et al, 2012;Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%